Power dependent nonlinear optical characteristics and two-photon absorption of NiO/PVA thin film. Issue 1 (1st October 2022) - Kumar, V Pradeep; Pradeep, C; Radhakrishnan, P; Mujeeb, A
Abstract : The NiO/PVA thin film was prepared by drop-casting the nickel oxide nanoparticles synthesized by the chemical precipitation method. The structural and optical characteristics of the film were investigated using XRD and UV-VIS absorption. The nonlinear optical property of the Nickel oxide thin film was studied by the open aperture Z-scan method at 532 nm. The two-photon absorption coefficient of the film was calculated with different optical intensities. With increasing input intensity, the value of the two-photon absorption coefficient has decreased. This is attributed to the saturation of two-photon absorption mechanism. The NiO/PVA film can be used for optical limiting applications.